Intervenção de terapia ocupacional com mães acompanhantes na enfermaria pediátrica - Souza, Lucas Ramon Santos de (Universidade Federal de São Carlos, 2021)
Accompanying mothers have been the target of interventions and research by occupational therapists. In the hospital context, the contributions of Occupational Therapy assistance to accompanying mothers have demonstrated the importance of occupational therapists in coping with the difficulties resulting from hospitalization. To know the intervention of the occupational therapist with accompanying mothers during the hospitalization of their children in a pediatric ward. This is a cross-sectional, descriptive, exploratory study with a qualitative approach. The research took place through access to an online questionnaire, using the Google Forms® tool. The self-administered questionnaire had 39 open-ended and closed-ended questions. Quantitative data were analyzed using simple descriptive statistics and for data resulting from open questions, the Content Analysis technique was used in the thematic mode, with the aid of the qualitative analysis software ATLAS.ti®. 14 occupational therapists participated in the study, predominantly female, in the age group up to 39 years, training time between 12 and 19 years and in the Southeast region. From the analysis of the data, the results are presented in three categories entitled: “Mothers accompanying their children in a pediatric ward - living this situation on a daily basis from the perspective of occupational therapists”, which refers to the understanding of the participants regarding the experienced child hospitalization by mothers and the repercussions on daily life; “Intervention processes in assisting accompanying mothers”, which includes the evaluations, objectives, and contributions of the interventions; in addition to the references, resources, techniques and spaces used in occupational therapeutic care; and “The difficulties and challenges of the practice of Occupational Therapy in assisting accompanying mothers in a pediatric ward”, which includes the prioritization of pediatric care, the absence of assessment tools, scarcity of resources and little availability of physical space to assist this population. The occupational therapists have been providing assistance in the pediatric ward with comprehensive care, including accompanying mothers and the mother-child dyad in interventions. Finally, it is pointed out that the present study contributes to the production of knowledge about the practices of Occupational Therapy in Hospital Contexts and in the development of assistance directed to accompanying mothers in a pediatric ward.
Intervention of occupational therapy with accompanying mothers in pediatric nursing
Keywords: Enfermaria pediátrica; Hospitalização; Intervenção; Mães; Saúde da mulher; Terapia ocupacional; Pediatric nursery; Hospitalization; Intervention; Mothers; Women's health; Occupational therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL